Is the Fermi‐level pinned on InN grown surfaces?. Issue 3 (20th February 2014) - Zhao, Songrui; Mi, Zetian
Abstract: In this paper, we discuss the Fermi‐level pinning issue on InN grown surfaces, in particular the nonpolar m ‐planes. Detailed angle‐resolved X‐ray photoelectron spectroscopy studies show that for intrinsic InN nanowires the Fermi‐level on the nonpolar grown surfaces is located 0.1 to 0.2 eV below the conduction band edge, i.e., not pinned in the conduction band. This indicates that the commonly measured Fermi‐level pinning in the conduction band on nonpolar grown surfaces is not an intrinsic property of InN. Furthermore, our studies also suggest that surface states are positioned near the band edge and therefore do not contribute to the Fermi‐level pinning. This is consistent with recent theoretical and experimental studies. In the end, with the absence of the Fermi‐level pinning in the conduction band and surface electron accumulation, the unique electrical and optical properties of intrinsic InN nanowires are discussed, and compared with previously reported InN epilayers and n ‐type InN nanowires. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)